1984
DOI: 10.3171/jns.1984.61.5.0864
|View full text |Cite
|
Sign up to set email alerts
|

Outcome in 60 consecutive patients treated with early aneurysm operation and intravenous nimodipine

Abstract: Sixty consecutive patients with a ruptured supratentorial aneurysm underwent operation during the acute stage, 56 of them within 72 hours after the first bleed, one on the 4th day, and three on the 5th day. Six patients were classified preoperatively in Hunt and Hess neurological Grade I, 39 in Grade II, 11 in Grade III, and four in Grade IV or V. Nine patients had severe intracerebral hematomas, and one patient had a subdural hematoma. After the aneurysm was clipped, nimodipine was applied to the exposed arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
2

Year Published

1986
1986
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(40 citation statements)
references
References 27 publications
3
35
0
2
Order By: Relevance
“…The present study indicates that there is no direct correlation between vasospasm in large intracranial arteries and impaired CBF autoregulation, as the incidence of angiographically demonstrable vasospasm is not influenced by nimodipine treatment 4,8,17,22,27 It should be underlined, that even if nimodipine treatment might improve CBF autoregulation in SAH patients, it is still dangerous to allow extensive MABP fluctuations, especially because the shape of the autoregulation curve in every single patient is unknown. From experimental results it seems reasonable to expect a more pronounced effect on CBF autoregulation if treatment with nimodipine is initiated early after the onset of SAH 7.…”
Section: Nimodipine and Cbf Autoregulationmentioning
confidence: 87%
“…The present study indicates that there is no direct correlation between vasospasm in large intracranial arteries and impaired CBF autoregulation, as the incidence of angiographically demonstrable vasospasm is not influenced by nimodipine treatment 4,8,17,22,27 It should be underlined, that even if nimodipine treatment might improve CBF autoregulation in SAH patients, it is still dangerous to allow extensive MABP fluctuations, especially because the shape of the autoregulation curve in every single patient is unknown. From experimental results it seems reasonable to expect a more pronounced effect on CBF autoregulation if treatment with nimodipine is initiated early after the onset of SAH 7.…”
Section: Nimodipine and Cbf Autoregulationmentioning
confidence: 87%
“…There is increasing evidence to suggest that despite its ability to reduce the incidence of cerebral infarct and neuronal deficit, nimodipine does not reduce the spasm visualized by angiography. 45,46 However, only the larger arteries are detected by angiography, and it is not clear whether nimodipine has some effect on the smaller pial arteries. Given the possible involvement of ET in cerebral vasospasm, we investigated the effect of nimodipine on responses to ET-1 in human small pial arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Nimodipine (Bay e 9736) is a dihydropyridine that has been intensively studied because of its apparently selective effects on cerebral vessels Kazda and Towart, 1982). Clinical trials have shown beneficial effects of nimodipine in the treatment of subarachnoidal haemorrhage (Allen et aL, 1983;Ljunggren et aL, 1984), migraine (Gelmers, 1983;Meyer and Hardenberg, 1983) and stroke (Gelmers, 1984). Furthermore, the drug improves neurological recovery after complete cerebral ischemia in animals Steen et al, 1984; for review of the pharmacological effects of nimodipine see Scriabine et aL, 1985).…”
Section: Introductionmentioning
confidence: 99%